India and central Asia - Liu, Xinru (ed.) (Ranikhet, 2012)
Central Asia has been a strategic region in world history because of its location in the Afro-Eurasian land mass, and because it was the hinge between several different ecological zones. From the border of the Iranian plateau to the edge of the Takla Makan desert, and from the foothills of the Kunlun Mountains to the Taiga zone of Siberia, Central Asia encompasses peoples who spoke many languages and practised various forms of livelihood. For historians who have been focused on individual civilizations, or the societies which have left written records, Central Asia has seemed an ocean full of dark energy. From time to time, barbaric nomads flew out from Central Asia to loot villages and destroy cities in East and South Asia, and even Europe. In recent decades, research on the lives of nomadic people on the steppe, archaeological excavations of urban settlements on oases along the Amu and Sir rivers, and the discovery of more Hellenistic remains have made scholars look at this region from a different perspective. Looking towards Central Asia from the Indian subcontinent shows that the dynamics in Central Asia were often the momentum for fundamental changes in history which brought new cultural elements to South Asia.
Keywords: India-Foreign relations-Central Asia